Prognostic factors of Bell's palsy: Multivariate analysis of electrophysiological findings. (10th June 2014) - Mancini, Patrizia; De Seta, Daniele; Prosperini, Luca; Nicastri, Maria; Gabriele, Maria; Ceccanti, Marco; Sementilli, Giulio; Terella, Maria; Bertoli, Gian Antonio; Filipo, Roberto; Inghilleri, Maurizio
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The study was designed to verify if one or more electrophysiological parameters could predict a risk of nonrecovery of normal facial function and the development of synkinesis in Bell's palsy (BP) subjects. Study Design Prospective case series. Methods A total of 120 subjects ranging from 18 to 70 years with unilateral BP (International Classification of Disease‐11), Grade III to VI House‐Brackmann (HB) degree, were assessed and treated with standardized oral steroids and antiviral drugs within 48 hours from onset. Of these, 92 underwent electroneurography (ENoG), electromyography (EMG), and blink reflex (BR) testing at 7 to 10 and 20 days after palsy onset. Multivariate analysis and receiver operating characteristic curves were carried out to verify which combination of electrophysiological parameters may be predictive of no recovery and/or development of synkinesis. Results BR and ENoG were the best predictors of no facial function recovery, showing significant correlation coefficient with severity of facial palsy in both assessments. EMG findings did not add any prognostic significance. Worsening of facial palsy can be observed in subjects despite steroid therapy. The risk of developing synkinesis might be evaluated soon after BP on the grounds of ENoG degeneration, orbicularis oculi denervation, a younger age, and severe (V–VI) HB grade. Conclusions BR and ENoG, considered together with clinical findings, could offer a good indication in the first phases of BP for the possibility to develop palsy residua. This combination of tests is well accepted by the subjects, and is therefore suitable for multiple assessments in the early postpalsy period.Key Words: Bell's palsy, facial palsy, ENoG, blink reflex, Prognosis. Level of Evidence 4. Laryngoscope, 124:2598–2605, 2014